TRAINING OF GROWTH RECORD CHANGES A BEHAVIOUR FOR POSYANDU'S CADRES - Nursalam Nursalam; Dinna Agustina; Ni Ketut Alit Armini (Universitas Airlangga, 2017)
Introduction: Most Posyandu's cadres cannot fill growth record of children correctly due to lack of training. The objective of this study was to explain the effect of training about growth record filling to behaviour changing of Posyandu cadres. Method: This research used quasy experimental method. The population of this research were all Posyandu cadres. Sample was taken by simple random sampling then 20 respondents divided into treatment group and control group. Independent variable in this research was the training for cadres filling growth record of children and dependent variable was the behaviour changing of Posyandu's cadres. Data were taken by using the questionnaire and directly the interview to respondent then be analyzed by using Wilcoxon Signed Ranks Test and Mann Whitney U Test, with signi fi cant level α ≤ 0.05. Result: The result showed that training for cadres about filling growth record had significant effect to the cadre's behaviour (knowledge α = 0.007, attitude α = 0.005, and action α = 0.007). But, it had no signi fi cant effect on control group (knowledge α = 0.157, attitude α = 0.102, action α = 1.00). Discussion: It can be concluded that training of cadre about filling growth record could change the Posyandu's cadres behaviour. Public health centers need to conduct training which have compatible content with the standard of Government Health Departement. Further studies should involve larger respondents to obtain more accurate result.